The trajectory of fear of birth during and after pregnancy in women living in a rural area far from the hospital and its labour ward - Ingegerd Hildingsson (James Cook University, 2021)
Introduction: There is a growing interest in fear of childbirth. The prevalence, reasons and treatment have been investigated, but the development of fear of birth during and after pregnancy in a sample of women from a rural area is less studied. The aim of this study was to explore the trajectories of fear of birth and associated factors in a sample of women living in a rural area of Sweden. Methods: A longitudinal cohort study of women were recruited to a continuity-of-care project in mid-pregnancy and followed up 2 months after birth. Data were collected by two questionnaires. Fear of birth was assessed using the Fear of Birth Scale (FOBS) in mid-pregnancy, in retrospect after birth and looking forward to a possible future birth. Results: The questionnaire was completed by 280 women in mid-pregnancy and by 236 women after giving birth. The mean FOBS fluctuated over time: it was highest in pregnancy, lower after birth and then increased once more when women were thinking about a future birth. Factors associated with developing fear after birth were mainly related to having had an emergency caesarean section, epidural, augmentation, or neonatal care that resulted in a less positive birth experience. Reduction of fear was associated with antenatal support. For some women, the levels of fear did not change, and these women were characterised with worse self-rated health but also more negative experiences of having given birth. Conclusion: Fear of birth seemed to change over time and was associated with women's emotional wellbeing, circumstances accompanying the actual birth and the whole birth experience. Support during pregnancy could change the trajectory of fear of birth. Women whose levels of fear were high rated their health lower and had a more negative birth experience. More research is needed into how best to help women overcome their fear of birth.